2021
DOI: 10.3390/children8050378
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Nitric Oxide at Birth Reduces Pulmonary Vascular Resistance and Improves Oxygenation in Preterm Lambs

Abstract: Resuscitation with 21% O2 may not achieve target oxygenation in preterm infants and in neonates with persistent pulmonary hypertension of the newborn (PPHN). Inhaled nitric oxide (iNO) at birth can reduce pulmonary vascular resistance (PVR) and improve PaO2. We studied the effect of iNO on oxygenation and changes in PVR in preterm lambs with and without PPHN during resuscitation and stabilization at birth. Preterm lambs with and without PPHN (induced by antenatal ductal ligation) were delivered at 134 d gestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Inhaled nitric oxide (iNO) is a common therapy for newborns suffering from PPHN in the neonatal intensive care unit, but the potential effects of its use during stabilization and resuscitation immediately after birth have not been investigated in detail. In their animal study, Lakshminrusimha et al [ 5 ] studied the effects of iNO on oxygenation and pulmonary vascular resistance in preterm lambs with and without PPHN during resuscitation and stabilization at birth. They concluded that iNO at birth is effective for improving oxygenation and reducing pulmonary vascular resistance in both preterm lambs with and without PPHN without increasing inspired oxygen.…”
Section: Respiratory Supportmentioning
confidence: 99%
“…Inhaled nitric oxide (iNO) is a common therapy for newborns suffering from PPHN in the neonatal intensive care unit, but the potential effects of its use during stabilization and resuscitation immediately after birth have not been investigated in detail. In their animal study, Lakshminrusimha et al [ 5 ] studied the effects of iNO on oxygenation and pulmonary vascular resistance in preterm lambs with and without PPHN during resuscitation and stabilization at birth. They concluded that iNO at birth is effective for improving oxygenation and reducing pulmonary vascular resistance in both preterm lambs with and without PPHN without increasing inspired oxygen.…”
Section: Respiratory Supportmentioning
confidence: 99%